Cardiovascular Disease in Chronic Kidney Disease: Pathophysiological Insights and Therapeutic Options - Jankowski, Joachim; Floege, Jürgen; Fliser, Danilo; Böhm, Michael; Marx, Nikolaus (Circulation (New York, N.Y.), 2021)
Patients with chronic kidney disease (CKD) exhibit an elevated cardiovascular risk manifesting as coronary artery disease, heart failure, arrhythmias, and sudden cardiac death. Although the incidence and prevalence of cardiovascular events is already significantly higher in patients with early CKD stages (CKD stages 1-3) compared with the general population, patients with advanced CKD stages (CKD stages 4-5) exhibit a markedly elevated risk. Cardiovascular rather than end-stage kidney disease (CKD stage 5) is the leading cause of death in this high-risk population. CKD causes a systemic, chronic proinflammatory state contributing to vascular and myocardial remodeling processes resulting in atherosclerotic lesions, vascular calcification, and vascular senescence as well as myocardial fibrosis and calcification of cardiac valves. In this respect, CKD mimics an accelerated aging of the cardiovascular system. This overview article summarizes the current understanding and clinical consequences of cardiovascular disease in CKD.